Basketball course optimization based on mechanical characteristics - Ren, Y.; Feng, L. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction Currently, college basketball lacks evaluation criteria, making the teaching of many classes reduced to the study of superficial movements, preventing the optimization of the sport`s intrinsic mechanical characteristics. Objective Optimize the methodology of the basketball course by implementing the kinematic analysis of its key movements. Methods Four elite athletes were selected as research subjects. Infrared reflective balls were used as markers on the right elbow joint, right shoulder joint, left hip joint, right knee joint, right ankle joint, and left ankle joint, among other areas. The mechanical characteristics of the possession preparation phase, the ground takeoff phase, the takeoff stage, and the landing phase were compared, classified, and analyzed kinematically by APA software. The data were processed by SPSS software. Experimental data were classified and analyzed using independent variance, considering significant differences for P < 0.05. Results Differences in sports habits, physical conditions, and mechanical characteristics of elite athletes resulted in distinct joint angles, although within a common range. Conclusion When optimizing the basketball course, teachers should fully study the experience of professional athletes and update and optimize the basketball course for students from a more scientific and technical point of view for a better orientation in the sports teaching of the basketball course.